A colloidal gold immunochromatography for the detection of flumioxazin residues in fruits. Issue 10 (14th September 2022) - Wang, Peng; Xu, Xinxin; Liu, Liqiang; Song, Shanshan; Kuang, Hua; Xu, Chuanlai; Wu, Xiaoling
Abstract: In this study, an excellent monoclonal antibody (mAb) was produced that could sensitively and specifically recognize Flu in fruit samples. The mAb belonged to the IgG2 subclass and had a half‐inhibitory concentration (IC50 ) of 0.59 ng/ml and a limit of detection (LOD) of 0.13 ng/ml. A cross‐reactivity test revealed that the mAb had good specificity for Flu. A gold nanoparticle‐based lateral‐flow immunochromatographic (ICA) strip was used for the rapid screening of Flu in fruit samples. The method had a visual cut‐off value of 10 µg/kg for Flu in three different fruit samples when evaluated with the naked eye. The LODs were 5.25, 3.13, and 4.64 µg/kg for Flu in apples, grapes, and oranges, respectively, as obtained with the aid of a strip scan reader. Therefore, this ICA strip assay represented a potential tool for the detection of Flu in fruit samples.